The Oxford history of the laws of England. - Baker, John H. (John Hamilton) (Oxford history of the laws of England ;, 2003)
This volume in 'The Oxford History of the Laws of England' covers the years 1483-1558, a period of immense social political, and intellectual changes which profoundly affected the law and its workings.